Sjögren's syndrome complicated with Fanconi syndrome and Hashimoto's thyroiditis: Case report and literature review. (June 2016) - Shi, Mingmin; Chen, Lei
We report a unique case of Sjögren's syndrome complicated with Fanconi syndrome and Hashimoto's thyroiditis in a 53-year-old Chinese woman, initially found to have proteinuria, fatigue and multiple old costal fractures. Distal tubular dysfunction is the most common renal damage in Sjögren's syndrome, while Fanconi syndrome (which is caused by proximal tubular dysfunction) and Hypothyroidism are rare complications of Sjögren's syndrome.